A customized nasal dilator and breather for patient with deviated nasal septum - Brajendra Singh Tomar; Shubhra Singh; Ambika Shrivastava; Sukhvinder Singh Noble (Wolters Kluwer Medknow Publications, 2024)
Nasal obstruction due to deviated nasal septum (DNS) is commonly defined as patient discomfort manifested as a sensation of insufficient airflow through the nose. The definitive treatment for a DNS is septoplasty, this customized nasal device can be used as an adjunct to treatment. And can be used as a breather until The patient receives or underwent definitive treatment. This device contains a nasopharyngeal airway tube and a customized nasal dilator, the nasopharyngeal airway tube is made of soft and elastic medical plastics, with good biocompatibility, without skin damage and allergy, which will be inserted inside. which will be inserted inside the affected nostril and it fits accurately between the septum and the lateral endonasal tissue, the nasal dilator which is composed of heat-cure acrylic resin helps to keep the nasopharyngeal airway in position withoutdislodging. The device also has an elastic band on both sides which can be worn like a mask by the patient. The nasopharyngeal tube of this device has a stopper that prevents the nasopharyngeal tube to go inside the nostril accidentally and the said tube is sterilizable and easily replaceable (even by the patient).